Akhlak Siswa Terhadap Pelatih Pencak Silat PSHT di Cabang Pamekasan: Studi Living Qur’an Surah Al-Kahfi Ayat 66 - Syamsuri; Siti Masrohatin; Mokhammad Miftahul Huda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the moral behavior of students toward martial arts trainers at Persaudaraan Setia Hati Terate (PSHT) Branch of Pamekasan from the perspective of the Living Qur’an study of Surah al-Kahfi verse 66 and to identify the positive impacts of these moral values. This research employed a qualitative approach with a phenomenological research design. Data were collected through observation, interviews, and documentation. The research subjects consisted of the head of PSHT, trainers, and students of PSHT Pamekasan Branch. The findings revealed that students’ moral conduct toward trainers was reflected in attitudes of humility (tawadhu’), greeting and shaking hands, speaking politely, being patient, avoiding arrogance, and not interrupting trainers while they were giving instructions. In addition, students were accustomed to maintaining spiritual preparedness through ablution and prayer before training sessions began. These practices reflect the implementation of the values contained in Surah al-Kahfi verse 66 regarding the ethics of students toward teachers. This study also found that students’ moral behavior had positive impacts on trainers, parents, and society. For trainers, students’ politeness and discipline created a comfortable and conducive training atmosphere. For parents, the moral guidance provided in PSHT helped shape children into more responsible individuals who respect their parents. Meanwhile, in society, PSHT students were recognized as humble individuals who respect others and maintain good social relationships. Therefore, moral education in PSHT Pamekasan Branch not only develops martial arts skills but also strengthens students’ character and morality in everyday life.